Harvest point and maturation of camu‑camu fruit harvested at different stages - Pinto, Patrícia Maria; Jacomino, Angelo Pedro; Silva, Simone Rodrigues da; Andrade, Carolina Amanda Wippich (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to determine the harvest point and to characterize the postharvest of camu‑camu (Myrciaria dubia) fruit harvested at different maturity stages. The fruits are harvested at four maturity stages, defined by skin color: green, reddish‑green, red‑greenish, and purple. Fruit were cold‑stored at 22±1°C and 85±5% RH. It was used a completely randomized design, split‑potted in time, with five storage periods: 0, 3, 6, 9, and 12 days. Evaluations were made for: respiratory activity; ethylene production; skin color, determined with the hue angle and chromaticity coordinates a* and b*; firmness; fresh matter weight loss; contents of chlorophyll, anthocyanins, soluble solids, and ascorbic acid; titratable acidity; and rot incidence. Peaks of CO2 and ethylene production occurred after harvest. The contents of chlorophyll and anthocyanins varied according to the changes in skin color, from green to purple, which confirmed fruit ripening. The contents of ascorbic acid ranged from 759.02 mg per 100 g, in the green stage, to 1,071.12 mg per 100 g, in the purple one. Fruit harvested with complete purpled skin had reduced postharvest life. Best postharvest quality for camu‑camu is achieved when skin color is red‑green.